Параметри якості життя жінок з ендопротезованим кульшовим суглобом у післяпологовому періоді (абдомінальне пологорозрішення) як критерій ефективності програми фізичної терапії - Данильченко, С. І.; Канигіна, Світлана Миколаївна; Danylchenko, S. I.; Kanyhina, S. М. (My University, 2023)
Мета. Визначення параметрів якості життя жінок з ендопротезованим кульшовим суглобом у післяпологовому періоді як критерію ефективності програми фізичної терапії. Методи. Обстежено 9 жінок віком 28,5±1,6 років через 1 місяць після пологів, які відбулись шляхом кесаревого розтину. Розроблена програма фізичної терапії тривала 1 місяць. Застосовували терапевтичні вправи; функціональне тренування, PNF; масаж нижніх кінцівок, спини. Враховували рухові обмеження, пов’язані з неповністю сформованим рубцем після кесаревого розтину та з наявністю ендопротеза; відповідно створювали безпечні стратегії рухів, пов’язаних з доглядом за дитиною. Ефективність програми оцінювали за опитувальником SF-36. Результати. При первинному обстеженні у всіх жінок з ендопротезом у післяпологовому періоді було виявлено погіршення якості життя за SF-36. Різниця результатів фізичного компоненту здоров’я при первинному та повторному дослідженні за шкалою Physical Functioning становила 41,9%, Role-Physical – 39,4%, Bodily Pain – 26,0%, General Health – 42,2% (за всіма підшкалами отримано статистично значуще покращення стану жінок порівняно з вихідними параметрами (р<0,05)). Покращення психічного компоненту здоров’я у порівнянні із первинним результатом за шкалою Vitality становило 26,9 %, Social Functioning – 60,3%, Role-Emotional – 32,5%; Mental Health – 49,9% (за всіма підшкалами отримано статистично значуще покращення стану жінок порівняно з вихідними параметрами (р<0,05)). Methods. In the course of the study, 9 women aged 28.5±1.6 years were examined 1 month after childbirth, which took place by caesarean section. The developed program of physical therapy lasted 1 month (from the end of the first month after childbirth). In her process, therapeutic exercises for the trunk, upper and lower limbs were used; functional training to improve movements related to child care, Proprioceptive Neuromuscular Facilitation of lower limbs, back, trunk; massage of lower limbs, back. We took into account movement restrictions associated with an incompletely formed scar after cesarean section and with the presence of an endoprosthesis (excessive bending, rotation of the hip joint); accordingly, they created safe movement strategies related to child care (lifting, carrying) and transporting a baby carriage. Individual determination of short- and long-term goals of rehabilitation contributed to the improvement of psycho-emotional mood and increased compliance of women. The effectiveness of the tested program was evaluated using the standard SF-36 quality of life questionnaire («Medical outcomes study short form»). Results. During the initial examination, all women with hip arthroplasty in the postpartum period were found to have a deterioration in the quality of life according to the SF-36. Overloading of elements of the musculoskeletal system during pregnancy and changes in the biomechanics of a woman's body, which causes certain physical discomfort, is justified by hormonal and physical processes.During repeated testing, the effectiveness of the physical therapy program was confirmed by its positive impact on both scales - physical and mental functioning. The difference between the results of Physical health at the initial and repeated examination according to the Physical Functioning scale in the examined women was 41.9%, Role-Physical – 39.4%, Bodily Pain – 26.0%, General Health – 42.2%. Accordingly, for all subscales of Physical health, a statistically significant improvement in the condition of women was obtained compared to the initial parameters (р<0.05). The improvement of Mental health in comparison with the primary result on the Vitality scale in the examined women was 26.9%, Social Functioning - 60.3%, Role-Emotional - 32.5%; Mental Health - 49.9%. Therefore, a statistically significant improvement in the condition of women compared to the initial parameters was obtained for all subscales of Mental health (р<0.05).
Parameters of the quality of life of women with hip arthroplasty in the postpartum period (abdominal delivery) as a criterion for the effectiveness of a physical therapy program
Канигіна С. М. - ORCID ID: 0000-0002-8197-299X.
Keywords: фізична терапія; реабілітація; післяпологовий період; кесарів розтин; ендопротез суглоба нижніх кінцівок; physical therapy; rehabilitation; postpartum period; caesarean section; endoprosthesis of the joint of the lower limbs